Assessing collaboration in a web-based constructivist learning environment: A Malaysian perspective - Leow, Fui-Theng; Neo, Mai (2013)
This paper focuses on studying the students’ collaborative processes within a web-based learning environment. A constructivist web-based learning environment was designed using Jonassen’s (1999) CLE model, and centered around a multimedia group project and the use of web 2.0 tools. The project was undertaken by students at INTI International University, Malaysia, and worked in a project group of 4 members. This study assesses students’ perception, attitude change, language acts through the use of several data collection instruments, including questionnaires, open-ended questions, interview, and students’ interaction records in web-based applications. Factor analysis was performed on quantitative data, whereas the framework of CMCL was used to investigate the qualitative data to identify the collaboration and communication through their communicative acts during project development process. Results showed that group collaboration provided peer support, increased their motivation and satisfaction, and more communication and interaction were stimulated in the learning process.